Economic growth model, structural transformation, and green productivity in China - Li, Ke; Lin, Boqiang (Applied energy, 2017)
•Two total factor productivities of China are estimated by super-DEA models.•Investment-driven growth model produces the negative effect on green productivity.•Various structural transformation have different impacts on green productivity. This study investigates the impacts of investment-driven economic growth model, as well as rationalization and upgrading of the industrial structure on green productivity in 30 Chinese provinces over the period 1997–2010. Two total factor productivities (TFP), namely energy adjusted TFP and energy and carbon dioxide emissions adjusted TFP (denoted as TFEE and TFCE respectively), are estimated using super-efficiency DEA models, and used as indices to reflect green productivity performance in China. The main results of the empirical study are as follow: (1) China’s economic growth model does not improve both TFEE and TFCE; (2) the flow of laborers from the primary, secondary, and tertiary industries helps to improve TFEE and TFCE, while capital transformation does not produce the same effect; (3) the structural changes in the manufacturing industry produce negative and positive effects on TFEE and TFCE respectively.